PEMBELAJARAN INTEGRATIF DALAM MATAKULIAH MATERI DAN PEMBELAJARAN IPA SD DENGAN KONSEP DASAR IPA PADA MAHASISWA S1 PGSD UT SURABAYA - Surasmi, Wuwuh Asrining; Supardiyono, Supardiyono (LPPM Universitas Terbuka, 2014)
To improve the quality of science education in elementary first step is to improve the quality of teachers and prospective science teachers in primary schools, especially in teacher education institutions, one of which is in UT. This study aims to describe the first implementation model of integrative learning in the course material and tutorial activities Elementary Science Lesson with IPA Basic Concepts in the S-1 student PGSD pokjar Tuban. Secondly to describe the effectiveness of the implementation of integrative learning in the course material and tutorial activities Elementary Science Lesson with IPA Basic Concepts in improving the mastery of basic science concepts and the ability to plan student learning in the S-1 PGSD pokjar Tuban. Third to describe the influence of the implementation of integrative learning in the course material and tutorial activities Elementary Science Lesson with IPA Basic Concepts on learning achievement and course materials to students of elementary Science Lesson S-1 PGSD Pokjar Tuban. This research is the development of learning tools such as: Design Activity Tutorial (RAT), Unit Events Tutorial (SAT), Draft Evaluation (RE), and the Student Worksheet (MFI). Software development refers to the four D model proposed by Thiagarajan and Semmel (1974:6). Learning tools developed quite fit for use, can improve the ability to make lesson plans and student learning outcomes. Untuk meningkatkan kualitas pendidikan IPA di SD langkah pertama yang dilakukan adalah meningkatkan kualitas guru dan calon guru IPA di SD, khususnya di lembaga pendidikan guru, salah satunya adalah di UT. Penelitian ini bertujuan untuk pertama mendeskripsikan model implementasi pembelajaran integratif dalam kegiatan tutorial matakuliah Materi dan Pembelajaran IPA SD dengan Konsep Dasar IPA pada mahasiswa S-1 PGSD pokjar Kabupaten Tuban. Kedua untuk mendeskripsikan efektifitas implementasi pembelajaran integratif dalam kegiatan tutorial matakuliah Materi dan Pembelajaran IPA SD dengan Konsep Dasar IPA dalam meningkatkan penguasaan konsep dasar IPA dan kemampuan membuat perencanaan pembelajaran pada mahasiswa S-1 PGSD pokjar Kabupaten Tuban. Ketiga untuk mendeskripsikan besar pengaruh implementasi pembelajaran integratif dalam kegiatan tutorial matakuliah Materi dan Pembelajaran IPA SD dengan Konsep Dasar IPA terhadap prestasi belajar matakuliah Materi dan Pembelajaran IPA SD pada mahasiswa S-1 PGSD Pokjar Kabupaten Tuban. Penelitian ini merupakan penelitian pengembangan perangkat pembelajaran yang berupa: Rancangan Aktivitas Tutorial (RAT), Satuan Acara Tutorial (SAT), Rancangan Evaluasi (RE), dan Lembar Kerja Mahasiswa (LKM). Pengembangan perangkat mengacu pada four D model yang dikemukakan oleh Thiagarajan dan Semmel (1974:6). Perangkat pembelajaran yang dikembangkan cukup layak digunakan, dapat meningkatkan kemampuan membuat RPP dan hasil belajar mahasiswa.